Six new species of Handaoia Seyrig, 1952 (Hymenoptera, Ichneumonidae, Phygadeuontinae): the first to be described from the New World - Bordera, Santiago; Broad, Gavin R. (European Journal of Taxonomy, 2021)
Handaoia Seyrig, 1952 is a small genus of Phygadeuontinae currently represented by eleven described species from Madagascar, Tanzania and Europe, and can be recognized by the combination of the distally expanded and ventrally flattened antennal flagellum, complete posterior transverse carina of the mesosternum, isolated ‘pit’ (episternal scrobe) in the mesopleuron, and a single bulla in fore wing vein 2m-cu. Most species have a distinctive combined area basalis and area superomedia on the propodeum. The following six new species from Central and South America are described and illustrated: H. cuscoensis Bordera sp. nov. from Peru, H. fritzi sp. nov. from Brazil, H. mercedensis Bordera sp. nov. from Peru, H. plaumanni sp. nov. from Brazil, H. ruizcancinoi Bordera sp. nov. from Mexico, and H. urceus sp. nov. from Brazil. A key to the New World species is provided.